Physical and Chemical Characteristics of Wet Soil in Swamp Ecosystems: Implications for Sustainable Agriculture of Tidal Swamps in South Kalimantan - Murjani Murjani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research aims to analyze the physical and chemical characteristics of wet soils in tidal swamp ecosystems and their implications for sustainable agriculture in South Kalimantan. Tidal marshlands have great potential to be developed as agricultural land, but specific soil conditions require proper management. The results showed that soils in tidal marsh ecosystems are generally clay-textured with high moisture content and low porosity, which affects soil drainage and aeration. Moderately high organic matter content (3-7%) is a positive factor for soil fertility, but soil acidity (pH 4.5-5.5) and high sulfate content pose challenges for agriculture. Soil acidity potentially inhibits the availability of essential nutrients such as phosphorus and increases aluminum toxicity. The potential formation of acid sulfate soils also requires careful management to prevent further soil degradation.